A poverty dynamics approach to social stratification: The South African case. (October 2018) - Schotte, Simone; Zizzamia, Rocco; Leibbrandt, Murray
Highlights: The paper bridges the gap between middle class and poverty dynamics research. The proposed classification schema accounts for chances of poverty entry and exit. South Africa's stable middle class is smaller than most other studies suggest. Transient poor and vulnerable (but non-poor) households are structurally similar. For a stable middle class, the stability and quality of employment are essential. Abstract: The wave of upbeat stories on the developing world's emerging middle class has reinvigorated a debate on how social class in general and the middle class in particular ought to be defined and measured. In the economics literature, most scholars agree that being middle class entails being free from poverty, which means being able to afford the basic things in life – not only today, but also tomorrow. In consequence, there is an increasing tendency to define the middle class based on a lack of vulnerability to poverty. In this paper, we strengthen and expand on these existing approaches in three ways: First, we incorporate the differentiation between the middle class and a (non-poor) vulnerable group into a broader social-stratification schema that additionally differentiates between transient and chronic poverty. Second, in estimating the risk of poverty, we employ a multivariate regression model that explicitly allows for possible feedback effects from past poverty experiences and accounts for the potential endogeneity of initial conditions, unobserved heterogeneity, and non-random panel attrition – four factors insufficiently addressed in existing studies. Third, we highlight the value of paying attention to these conceptual and modelling issues by showing that class divisions based on monetary thresholds inadequately capture a household's chances of upward and downward mobility. We then apply our conceptual framework to the South African case. We find that only one in four South Africans can be considered stably middle class or elite. Access to stable labor market income is a key determinant of achieving economic stability. A lack of jobs as well as the prevalence of precarious forms of work drive high levels of vulnerability, which in turn constrains the development of an emergent middle class – not only in South Africa but potentially also in other parts of the developing world that face similar labor market challenges.